Evaluation the Effect of Different Instrumentation& Obturation Techniques on the Apical Sealing Using Two Types of Sealers (Mustansiria Dental Journal, 2018)
There is controversy as to which instrumentation &/or obturation techniques tochoose with which type of sealer give better apical sealing. This in vitro study aimedto evaluate the apical sealing ability of three obturation techniques and two types ofsealer.A total of 120 teeth were randomly divided into two groups; roots prepared usingstep-back and hybrid techniques. Each group of instrumented roots were subdividedrandomly into three obturation groups of 20 roots for each; each one of theseobturation techniques were used twice; once with ZOE sealer and other with AH26sealer. Then dye penetration study conducted & samples were examined under thestereomicroscope. Data had been collected from two independent examiners andstatistically analyzed using student t-test.Concerning the obturation techniques, warm vertical compaction showed bestapical sealing. Regarding sealers, AH 26 sealer had better sealing ability than ZOEsealer with highly significant difference.Warm vertical compaction obturation technique in combination with the AH 26resin sealer obturates the canals with lesser apical leakage.